The deaf person and the late acquisition of the Brazilian Sign Language: an analysis of practice - Guarany, Ann Letícia Aragão (2021)
This article emerged from a professional experience as a pedagogue in the development of work activities, specifically, with a deaf student from the rural area of a village in the city of Cedro de São João - SE, where the difficulties arising from school gaps, illiteracy and lack of preparation of the school and its professionals to work with inclusion, led to research on the process of visual literacy and literacy in Brazilian Sign Language (BSL), observation and reflection on the practice itself. The purpose of this article was to analyze the effects of late acquisition of Sign Language in the development of the deaf person from educational actions carried out in the literacy and socialization process in school. The methodology adopted was based on action-research and a qualitative approach, with students from the 4th year of lower elementary school, especially a deaf student, having the following steps: i) field recognition; ii) application of activities and evaluation, using observation, open interviews and field diaries and iii) data analysis. The results obtained showed the interest of the school community in learning BSL and interacting with the deaf student, however, the difficulties in language acquisition in this initial inclusion process were still quite significant. We consider the need to expand the debate on the issue and a direction based on the promotion of inclusive affirmative actions throughout the school, which enable educational training and allow specialized educational care for people who have been historically excluded by the listening society.